Use of the RAFT technique as an efficient method to synthesise well defined polymer-clay nanocomposites with improved properties - Samakande, Austin (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2009.